A instituição democrática do Tribunal do Júri e a Lei n. 13.964/2019 - Ianni, Gabriela de Castro (2021)
The Jury was designed to protect the freedom. It is an emblem of democracy, especially for the reception of the people within the judiciary. Given the relevance of the institution for democratic proposals, the study addressed the transformations implemented by Law 13.964/2019 with the sanctions imposed by the Jury, with a special attention to the immediate enforcement of convictions of fifteen years of imprisonment or more, even when there is appeal waiting for trial. The research’s main focus is the compatibility of the immediate enforcement settled in Article 492, I, of Code of Criminal Procedure, as well as the attribution, of the Jury President and the Appeal Courts, to prevent the immediate execution of the conviction, in the face of human rights, fundamental rights and guarantees, due process of law and the principle that no one can be found guilty until judgment of competent court; principles that are fundamental to the Constitution of the Federative Republic of Brazil